ANALISIS PELUANG DAN TANTANGAN ADANYA BONUS DEMOGRAFI DITAHUN 2045 TERHADAP PEREKONOMIAN INDONESIA - Nurul Qomariyah (Sahmiyya, 2023)
This study aims to analyze the opportunities and challenges of the demographic bonus in 2045 for the Indonesian economy. In conducting this research using a qualitative descriptive analysis method based on literature which contains citation data found in the field to support what is presented. The results of this study conclude that the demographic bonus in Indonesia will occur around 2045. The big problem due to the demographic bonus is due to a decrease in the birth rate and high death rate in the long term. The existence of a demographic bonus can also affect Indonesia's economic growth which in turn can increase the income of the wider community. In fact, the economic growth and income which is still relatively low is supported by public consumption. High and sustainable economic growth is needed to achieve an increase in people's welfare, besides that it also requires relatively large capital which will be used to strengthen infrastructure, both physical and social. The phenomenon of demographic bonus can be used as a big opportunity by utilizing human resources. Availability of productive age in large numbers can be a support for the government without hiring workers from outside. In addition, it can be a boomerang for the government if it cannot maximize human resources properly. Thus it is necessary to have a balance and quality education as a source of strength from the existence of a demographic bonus.